(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The disadvantage of the device that transports cotton with the help of air is the high consumption of electricity compared to the unit amount of transported material, and the rapid wear and failure of the working bodies, including the pipes, which are in direct contact with the transported material containing foreign bodies